STRATEGIC PLANNING IN INDUSTRIAL ENTERPRISES (American Journal of Business Management, Economics and Banking, 2024)
The article is devoted to the issues of strategic planning in industrial enterprises, including its role in improving efficiency and competitiveness in a market economy. The main stages and methods of strategy development, features of choosing the optimal strategy and its adaptation to changing environmental conditions are considered. Special attention is paid to the assessment of economic feasibility and risks in strategic planning. The paper also presents theoretical foundations, methods and approaches that can be applied to implement strategic planning in enterprises of Uzbekistan.